2018
DOI: 10.1590/1980-5373-mr-2016-0983
|View full text |Cite
|
Sign up to set email alerts
|

ZnS Nanocrystals as an Additive for Gamma-Irradiated Poly (Vinyl Chloride)

Abstract: Zinc sulfide (ZnS) was synthesized by sonochemical method and nanoparticles with crystallite size around 2 nm were obtained. PVC containing ZnS nanoparticles at concentrations of 0.10; 0.30; 0.50; 0.7 and 1.00 wt% were gamma irradiated ( 60 Co) at room temperature in air. No appreciable decrease in PVC Viscosity-Average Molar Mass (M v ) was observed for samples containing 0.7 wt% of ZnS nanocrystals. It was demonstrated that the addition of ZnS nanocrystals imparted molecular protection to the polymer matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The enhancement in the FL intensity, upon loading with ZnS/Mn, may be attributed to the presence of intermolecular interactions between the PVC molecules and ZnS. Sliva et al [43] attributed the changes in the C-Cl stretching FTIR peaks of the PVC/ZnS composite to the interaction between the PVC chlorine atom and ZnS, which is confirmed by the PCA (principal component analysis) of the FTIR pure PVC and PVC/ZnS spectra. A similar enhancement was observed for a PVA/ZnS composite [44], and for PVP-coated ZnS [45].…”
Section: Fluorescence Analysismentioning
confidence: 75%
“…The enhancement in the FL intensity, upon loading with ZnS/Mn, may be attributed to the presence of intermolecular interactions between the PVC molecules and ZnS. Sliva et al [43] attributed the changes in the C-Cl stretching FTIR peaks of the PVC/ZnS composite to the interaction between the PVC chlorine atom and ZnS, which is confirmed by the PCA (principal component analysis) of the FTIR pure PVC and PVC/ZnS spectra. A similar enhancement was observed for a PVA/ZnS composite [44], and for PVP-coated ZnS [45].…”
Section: Fluorescence Analysismentioning
confidence: 75%
“…Stabilizers like free radical scavengers (primary antioxidants) can prevent the main scission and cross-linking 13,21 . In addition, our most recent studies have shown the efficiency of using nanoparticles in the same amount of commercial additives as stabilizers for PMMA and Poly (vinyl chloride) (PVC) exposed to gamma radiation [22][23][24][25] .…”
Section: Commercial Additives For Polymer Matrixmentioning
confidence: 99%